PELAYANAN PASTORAL TERHADAP BUDAYA MUKAROI PAKTAPPIAM BOSIDI SUKU BAMBAN KABUPATEN MAMASA PROVINSI SULAWESI BARAT DAN IMPLIKASINYA BAGI KEHIDUPAN - Ulci Ulci; Adriani, Abigael Karurung, Putri Datu Arrang, Kristina (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The pastoral service of “ mukaroi paktappiam bosi” in this research is writing that aims to improve the habits of the Bamban tribe which still fosters the culture ofmukaroi paktappiam bosi which of course makes it difficult for a person's life, especially the community, to develop in a better future. The method that the author uses is qualitatively with approach a pastoral approach which is expected to help in resolving any problems caused by this culture. The author found that one of the problems that often arises in a person's life, especially in the Bamban community, ismukaroi paktappiam bosi. Therefore, these findings need to be followed up in research and pastoral care.